(untitled) (Research, Society and Development, 2022)
Palliative care aims to improve the quality of life of patients facing a life-threatening illness through the prevention and relief of suffering. The participation of the dental surgeon in the multidisciplinary team of palliative care is necessary, since the oral cavity can be directly or indirectly affected by different diseases and their treatments. Among patients who need palliative care, terminal cancer patients develop various oral manifestations such as xerostomia, mucositis and candidiasis. Considering all these factors, the objective of this work is to discuss the main oral manifestations that affect patients undergoing cancer treatment and some of the treatment options that aim to improve the quality of life of patients. It is concluded that the surgeon plays a fundamental role in maintaining the quality of life of patients, from diagnosis and prevention to care in the manifestations that may develop during antineoplastic treatment.